Clinical teaching and learning : an action research study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Schroyen, Bonnie Patricia Kay (Massey University, 2001)
For student nurses, the clinical setting is considered to be the most valuable and also the most complex learning situation of their professional education. There are currently many issues in New Zealand that affect the quality of experience available in clinical areas for these future nurses. This research was initiated by a polytechnic nursing lecturer to explore one teaching and learning situation in clinical settings with a group of student nurses in order to improve it. This study took place during an eleven week clinical block for the students in the last semester of a three year Bachelor of Health Science (Nursing) programme. The research question identified by the student participants was: "How can we improve the teaching and learning in clinical settings?" Using an educational action research model the students identified the essential elements in the situation in order to plan, implement and evaluate a practical change strategy. The main finding in the analysis was that the staff nurses have a major influence on the students' learning in clinical settings. Five staff nurses working closely with these students in clinical areas were included as the study widened to involve those affected by the proposed change. These staff nurses added their perspectives and these informed the planning phases. The students chose to introduce contract learning into their interactions with the staff nurses as a method to improve the teaching and learning in clinical settings. During the action phase it was discovered that because these students were working in diverse clinical areas and were developing unique learning relationships with the staff nurses, the method of implementing contract learning required innovation and perseverance. The individual experiences of these students, the staff nurses and a polytechnic lecturer are described as a case study of events. The action taken and the reflection on factors which hindered and which facilitated the success of contract learning are presented from the perspectives of all participants.
Keywords: Nursing; Nurses; Clinical medicine; New Zealand; Study; Training; Teaching